A single regulator mediates strategic switching between attachment/spread and growth/virulence in the plant pathogen Ralstonia solanacearum - Khokhani, Devanshi (2019)
The PhcA virulence regulator in the vascular wilt pathogen Ralstonia solanacearum responds to cell density via quorum sensing. To understand the timing of traits that enable R. solanacearum to establish itself inside host plants, we created a ΔphcA mutant that is genetically locked in a low-cell-density condition. Comparing levels of gene expression of wild-type R. solanacearum and the ΔphcA mutant during tomato colonization revealed that the PhcA transcriptome includes an impressive 620 genes (>2-fold differentially expressed; false-discovery rate [FDR], ≤0.005). Many core metabolic pathways and nutrient transporters were upregulated in the ΔphcA mutant, which grew faster than the wild-type strain in tomato xylem sap and on dozens of specific metabolites, including 36 found in xylem. This suggests that PhcA helps R. solanacearum to survive in nutrient-poor environmental habitats and to grow rapidly during early pathogenesis. However, after R. solanacearum reaches high cell densities in planta, PhcA mediates a trade-off from maximizing growth to producing costly virulence factors. R. solanacearum infects through roots, and low-cell-density-mode-mimicking ΔphcA cells attached to tomato roots better than the wild-type cells, consistent with their increased expression of several adhesins. Inside xylem vessels, ΔphcA cells formed aberrantly dense mats. Possibly as a result, the mutant could not spread up or down tomato stems as well as the wild type. This suggests that aggregating improves R. solanacearum survival in soil and facilitates infection and that it reduces pathogenic fitness later in disease. Thus, PhcA mediates a second strategic switch between initial pathogen attachment and subsequent dispersal inside the host. PhcA helps R. solanacearum optimally invest resources and correctly sequence multiple steps in the bacterial wilt disease cycle.